(untitled) (Journal of Bangladesh Institute of Planners, 2012)
This paper examined the impact of real property ownership on the systematic risk of hotel companies in Singapore. This issue is interesting because few studies have been carried out on this topic. The hypothesis is that the real estate ownership would impose negative effect on the systematic risk of company in hotel sector because corporate real estate is commonly considered as an instrument for diversification in a mixed portfolio. To examine the effect, two-stage least-square regression was applied. The data was collected from published sources and other data streams. The results indicate that real estate ownership has impact on the systematic risk of companies. The implication is that the different strategies of companies may result in the different directions of impacts. DOI: http://dx.doi.org/10.3329/jbip.v2i0.9579 Journal of Bangladesh Institute of Planners Vol. 2, December 2009, pp. 193-200